Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep38347
|View full text |Cite
|
Sign up to set email alerts
|

Loss of EGFR-ASAP1 signaling in metastatic and unresectable hepatoblastoma

Abstract: Hepatoblastoma (HBL), the most common childhood liver cancer is cured with surgical resection after chemotherapy or with liver transplantation if local invasion and multifocality preclude resection. However, variable survival rates of 60–80% and debilitating chemotherapy sequelae argue for more informed treatment selection, which is not possible by grading the Wnt-β-catenin over activity present in most HBL tumors. A hypothesis-generating whole transcriptome analysis shows that HBL tumors removed at transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Li et al demonstrated that PIM3 induced stemness via activation of the STAT3 pathway [23]. The STAT3 pathway has not been studied in hepatoblastoma aside from the understanding that STAT3 signaling is present [24,25]. Additionally, many of the pathways through which we have already demonstrated PIM3 to play a role in hepatoblastoma tumorigenicity are related to characteristics of SCLCCs.…”
Section: Discussionmentioning
confidence: 91%
“…Li et al demonstrated that PIM3 induced stemness via activation of the STAT3 pathway [23]. The STAT3 pathway has not been studied in hepatoblastoma aside from the understanding that STAT3 signaling is present [24,25]. Additionally, many of the pathways through which we have already demonstrated PIM3 to play a role in hepatoblastoma tumorigenicity are related to characteristics of SCLCCs.…”
Section: Discussionmentioning
confidence: 91%
“…PLK3 a, b refer to different Affymetrix probes. (C) mRNA expression data from Ranganathan, et al [23]. Fold change was found to be statistically significantly different from a hypothetical value of 1 by student’s t -test, p =0.0024.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, RNA expression was analyzed by microarray from tumor (n=25) and normal (n=4) [22]. A third study performed RNA sequencing for tumor (n=10) and normal (n=3) [23]. In all three sets of data, PLK1 was overexpressed (absolute mean expression 1.51 TPM ± 0.25 SEM, 6.49±0.13 and 1.95±0.36, respectively) with 1.9±0.28 average fold change between tumor and normal (Figure 2A) from the first study, with 1.05± 0.02 fold change (Figure 2B) from the second study and 4.19±0.08 fold change from the third study (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…In this conducted network, we identified two genes in epidermal growth factor (EGF) signaling, EGFR and SDC1 [ 40 ], acting as effector genes. Recently, a whole transcriptome analysis based on HB patients suggested that aberrant EGF signaling was associated with HB classification [ 41 ]. The loss of EGFR signaling members were shown to be more present in less differentiated embryonal and undifferentiated small cells subtypes of HB.…”
Section: Discussionmentioning
confidence: 99%